Unraveling the Political Motives of Eritrea in the Tigray Conflict - Noverino Faiz Adi Muhammad; Galvin Hapsari Putri; Dhika Fadhlan Aulia; Septyanto Galan Prakoso (Andalas Institute of International Studies UNAND, 2024)
Eritrea is one of the countries that has a significant influence in the Horn of Africa. In maintaining its influence and achieving its national interest, Eritrea has enrolled itself in the Tigray War. Participating in the Tigray War would drive themselves to be the regional superior in the Horns of Africa. This research will focus on how Eritrea's political motives in the Tigray War affected the achievement of its interests. This study will use the national interest concept and geopolitical theory to analyze the formulation of the problem that has been described. These theoretical frameworks will be suitable as these theoretical frameworks will be able to explain Eritrea’s national interest in the African Region. This research will also use qualitative methods and literature study data collection techniques. The results of this study suggest that Eritrea has political motives to be able to escape its international isolation status and become a regional superior in the Horn of Africa region. Eritrea also wants to expand its influence in Ethiopian domestic politics and avenge itself on the Tigrayan People's Liberation Front (TPLF) through its involvement in the Tigray war. Eritrea used a hawkish approach offensively in its involvement in the Tigray conflict.